Normal Uptake of (11)C-Acetate in Pancreas, Liver, Spleen, and Suprarenal Gland in PET - Malkowski, Bogdan (Can J Gastroenterol Hepatol, 2017)
PURPOSE: (11)C-Acetate is radiotracer being considered an alternative to (18)F-fluorodeoxyglucose. Evaluation of (11)C-acetate biodistribution in human parenchymal organs is described. METHODS AND MATERIALS: 60 consecutive patients referred to (11)C-acetate PET CT suspected of renal or prostate cancer relapse with negative results (no recurrent tumor) were included in the study. Acquisition from the base of skull to upper thigh was made 20 min after i.v. injection of 720 MBq of (11)C-acetate. The distribution was evaluated by measuring the uptake in pancreas (uncinate process and body separately), liver, spleen, and left suprarenal gland. Clinical data of included patients showed no abnormalities in these organs. RESULTS: Biodistributions of (11)C-acetate radiotracer were compared in different organs. Standardized uptake values of (11)C-acetate were significantly higher in pancreatic parenchyma (SUV mean 6,4) than in liver (SUV mean 3,3), spleen (SUV mean 4,5), or suprarenal gland (SUV mean 2,7) tissues. No significant difference was found between pancreatic head (SUV mean 6,4) and body (SUV mean 5,9) uptake. In case of all aforementioned organs, there were no differences either between both sexes or between formerly diagnosed tumors (renal and prostate). CONCLUSIONS: Evaluation of (11)C-acetate uptake differences in parenchymal organs will allow establishing normal patterns of distribution. High pancreatic uptake may be used in quantitative assessment of organ function in diffuse nonneoplastic pathology.